Yin (Good) Yang (Evil) Formula in the Power and the Glory by Graham Greene - Salam Hussein, Jegr; Ismail Radam, Halima (International Journal of Psychosocial Rehabilitation, 2020)
From the very beginning, human started to understand things on the base of opposites. This label of understanding his or her surrounding leads him or her to contemplate on the essence of this understanding and the big question of what good and evil are and how do they work and how do they affect human life is among the cardinal ones. That is why, the struggle between good and evil (Yin and Yang) is the fundamental question of all human activities. Among all human activities, literature concerns with the question more than any other fields. Therefore, the present paper sheds light on the conflict between good and evil through a philosophical icon which is known as “Yin Yang”. From this perspective, the struggle is dealt with on different levels in Graham Greene’s masterpiece, The Power and The Glory. Thus, the present paper is divided into four sections. The first section is an introduction. The second section depicts the philosophical icon of Yin (Good) Yang (Evil) formula. The third section studies the Yin Yang formula in the novel. Finally, there is a conclusion.